The Implementation of the Mind Mapping Method in Learning Arabic for Eighth-Grade Students at Raudhatul Hasanah Institute, Medan - Shandi, Kiki Haura; Salamuddin ((الطموحات ) EL-THUMUHAT, 2026)
Abstract This study aims to analyze the implementation of the mind mapping method in teaching Arabic to eighth-grade students at Raudhatul Hasanah Islamic Institute. The research employed a descriptive qualitative approach through a case study design, with data collected through observations and interviews with ten randomly selected eighth-grade students. The findings indicate that the application of the mind mapping method helps students understand Arabic learning materials in a more organized and accessible manner, particularly in developing their vocabulary and comprehending lesson topics. In addition, the method received a positive response from students, as it enhanced their engagement and interest in learning during the instructional process. However, the study also identified several challenges, such as some students’ difficulty in identifying key words and the limited instructional time, which necessitates ongoing guidance and training to ensure the optimal implementation of the mind mapping method. Overall, the mind mapping method can be considered an effective alternative in teaching Arabic to eighth-grade students. Keywords: implementation, mind mapping, Arabic language teaching